Analisys of government policy based on permenag number 31 of 2023 to close tiktok shop in an effort to save conventional traders in Indonesia - Eli Apud Saepudin; Gatot Hartoko; Rossa Amelia Putri (Institute Of computer Science (IOCS), 2024)
Tiktok shop is an additional feature launched by Tiktok to facilitate content creators, as an innovative social commerce that can reach producers, sellers, buyers and creators in providing a cheap and easy shopping experience without shipping costs with the Tiktok shop feature brand producers and sellers are enabled to grow their business through live shopping that they can collaborate with content creators. Tiktok shop was present on April 21, 2021 and closed on October 4, 2023. The problem faced since the presence of Tiktok shop is the loss of conventional traders such as the Tanah Abang market which is empty of visitors because people prefer to wait for groceries from home to arrive safely. Based on Permendag No. 31 of 2023, Tiktok shop was officially closed on the grounds that it was detrimental to conventional traders in Tanah Abang, the live feature on Tiktok shop provides a large profit for online sellers, Tiktok shop is only used as a promotion, there are regulations governing new technology. the method used in this research is a qualitative descriptive analysis method, namely by analyzing, describing, and analyzing.